مدى تطبيق الاختبارات الإلكترونية وتطويرها لدى المعلمين في مدارس الحلقة الثانية في محافظة الداخلية بسلطنة عمان / إعداد، سلام بن ناصر بن سلام الحوسني - حوسني، سلام ناصر سلام (Kulliyyah of Education, International Islamic University Malaysia, 2022)
The study aimed to identify the reality of using electronic exams among teachers in Second Cycle Schools in Ad-Dakhiliyah Governorate, Sultanate of Oman. The study community consisted of all teachers of the second cycle of basic education in Ad-Dakhiliyah Governorate, Sultanate of Oman and they were 5871 teachers, while the study sample included 361 teachers. The researcher adopted the quantitative descriptive approach as the study method and used the questionnaire as the study tool. The study came up with several findings including that the extent of the use of e-Exams came with a (medium) response degree and this can be explained by the fact that teachers still rely on the traditional method in the evaluation process, and it may be due to the poor availability of many means that help them use modern tools in the educational process and rely on e-Exams. The study recommended several recommendations including the necessity of holding training courses for teachers to use essay questions in designing electronic articles and taking into account the individual differences of students while designing electronic exams.